Angiotensin-converting enzyme insertion/deletion polymorphism and risk of restenosis after directional coronary atherectomy followed by stent implantation - Canosi, Umberto; Merlini, Piera Angelica; Bernardi, Francesco; Repetto, Alessandra; Bramucci, Ezio; Ferrario, Maurizio; Angoli, Luigi; Gnecchi, Massimiliano; Ferraresi, Paolo; Marchetti, Giovanna; Tavazzi, Luigi; Ardissino, Diego (Thrombosis and Haemostasis, 2004)
The D allele of the insertion/deletion (I/D) polymorphism of the angiotensin I-converting enzyme (ACE) gene is associated with higher plasma and tissue ACE levels, which enhance the stimulus for neo-intimal hyperplasia. Plaque debulking before stenting reduces the plaque-related determinants of in-stent restenosis and provides an ideal clinical model for studying neointimal hyperplasia. We prospectively studied 113 consecutive patients undergoing elective DCA followed by stent implantation. The presence of I/D in ACE genome DNA was analysed by means of polymerase chain reaction. Follow-up coronary angiography was performed 6-12 months after DCA, and all of the angiograms were quantitatively analysed. The baseline clinical and angiographic characteristics of the patients with a D/D (33%), I/D (52%) and I/I (15%) genotype were well balanced. There were no significant differences in minimal lumen diameter before and after the procedure or at follow-up, and no significant differences in acute gain, late loss or the loss index. Our results indicate that ACE I/D polymorphism does not influence the risk of developing angiographic restenosis in patients undergoing DCA followed by stent implantation.
Keywords: ACE-gene polymorphism; restenosis; stent; directional coronary atherectomy